2016
DOI: 10.1021/acscentsci.6b00184
|View full text |Cite
|
Sign up to set email alerts
|

Lasso Peptide Biosynthetic Protein LarB1 Binds Both Leader and Core Peptide Regions of the Precursor Protein LarA

Abstract: Lasso peptides are a member of the superclass of ribosomally synthesized and posttranslationally modified peptides (RiPPs). Like all RiPPs, lasso peptides are derived from a gene-encoded precursor protein. The biosynthesis of lasso peptides requires two enzymatic activities: proteolytic cleavage between the leader peptide and the core peptide in the precursor protein, accomplished by the B enzymes, and ATP-dependent isopeptide bond formation, accomplished by the C enzymes. In a subset of lasso peptide biosynth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 33 publications
3
37
1
Order By: Relevance
“…However, subsequent analysis revealed that only ∼4,000 of these sequences co-occur with the requisite leader peptidase and lasso cyclase. This number is more consistent with the most recent lasso peptide survey, which reported ∼3,000 lasso peptide BGCs ( 23 , 41 ). Proteins retrieved by the discrete lasso peptide model often co-occur with other common RiPP enzymes, such as rSAM enzymes which represent ∼300 of the false positives.…”
Section: Resultssupporting
confidence: 89%
“…However, subsequent analysis revealed that only ∼4,000 of these sequences co-occur with the requisite leader peptidase and lasso cyclase. This number is more consistent with the most recent lasso peptide survey, which reported ∼3,000 lasso peptide BGCs ( 23 , 41 ). Proteins retrieved by the discrete lasso peptide model often co-occur with other common RiPP enzymes, such as rSAM enzymes which represent ∼300 of the false positives.…”
Section: Resultssupporting
confidence: 89%
“…This number is more consistent with the most recent bioinformatic survey of lasso peptides, which reported ~3,000 lasso peptide BGCs with discretely encoded RREs 24,42 . Proteins retrieved by this model often co-occur with other common RiPP enzymes, such as rSAM enzymes (which represent ~300 of the "false positive" BGCs).…”
Section: Defining the Scope Of Rre-dependent Ripp Bgcssupporting
confidence: 89%
“…14 This fold is maintained by bulky side chains positioned above and below the ring sterically trapping the tail inside. Lasso peptide biosynthesis usually requires three to four gene products (Figure 1): 13, 510 the precursor peptide A consists of an N-terminal leader and a C-terminal core region. The leader region is required for enzymatic recognition, while the core region is converted into the mature lasso peptide.…”
mentioning
confidence: 99%